Randomized Phase II Trial of Parsatuzumab (Anti‐EGFL7) or Placebo in Combination with FOLFOX and Bevacizumab for First‐Line Metastatic Colorectal Cancer - García‐Carbonero, Rocío; van Cutsem, Eric; Rivera, Fernando; Jassem, Jacek; Gore, Ira; Tebbutt, Niall; Braiteh, Fadi; Argiles, Guillem; Wainberg, Zev A.; Funke, Roel; Anderson, Maria; McCall, Bruce; et al. (The oncologist (Dayton, Ohio), 2017)
Lessons Learned These negative phase II results for parsatuzumab highlight the challenges of developing an agent intended to enhance the efficacy of vascular endothelial growth factor inhibition without the benefit of validated pharmacodynamic biomarkers or strong predictive biomarker hypotheses. Any further clinical development of anti‐EGFL7 is likely to require new mechanistic insights and biomarker development for antiangiogenic agents. Background EGFL7 (epidermal growth factor‐like domain 7) is a tumor‐enriched vascular extracellular matrix protein that supports endothelial cell survival. This phase II trial evaluated the efficacy of parsatuzumab (also known as MEGF0444A), a humanized anti‐EGFL7 IgG1 monoclonal antibody, in combination with modified FOLFOX6 (mFOLFOX6) (folinic acid, 5‐fluorouracil, and oxaliplatin) bevacizumab in patients with previously untreated metastatic colorectal cancer (mCRC). Methods One‐hundred twenty‐seven patients were randomly assigned to parsatuzumab, 400 mg, or placebo, in combination with mFOLFOX6 plus bevacizumab, 5 mg/kg. Treatment cycles were repeated every 2 weeks until disease progression or unacceptable toxicity for a maximum of 24 months, with the exception of oxaliplatin, which was administered for up to 8 cycles. Results The progression‐free survival (PFS) hazard ratio was 1.17 (95% confidence interval [CI], 0.71–1.93; p = .548). The median PFS was 12 months for the experimental arm versus 11.9 months for the control arm. The hazard ratio for overall survival was 0.97 (95% CI, 0.46–2.1; p = .943). The overall response rate was 59% in the parsatuzumab arm and 64% in the placebo arm. The adverse event profile was similar in both arms. Conclusions There was no evidence of efficacy for the addition of parsatuzumab to the combination of bevacizumab and chemotherapy for first‐line mCRC. 经验总结 • Parsatuzumab的II期试验获得了一系列阴性结果, 这突显了在缺乏经验证的药效学生物标志物或高度预测性生物标志物假设的背景下, 开发旨在增强血管内皮生长因子抑制疗效的药物将面临严峻挑战。 • 如要在临床上进一步开发EGFL7抗体, 可能需要从新的角度深入了解抗血管生成药物的机制, 且需要开发相应的生物标志物。 摘要 背景. EGFL7（表皮生长因子样结构域蛋白7）是肿瘤血管内的一种细胞外基质蛋白, 可支持内皮细胞存活。本项II期试验评价了人源化抗EGFL7 IgG1 单克隆抗体Parsatuzumab（又称为MEGF0444A）与改良FOLFOX6（mFOLFOX6；亚叶酸、5‐氟尿嘧啶和奥沙利铂）和贝伐单抗联合治疗既往未经治疗的转移性结直肠癌（mCRC）患者的疗效。 方法. 对127例患者进行随机分配, 接受Parsatuzumab 400 mg或安慰剂与mFOLFOX6和贝伐单抗5 mg/kg联合治疗。以2周为一个治疗周期重复给药, 直至出现疾病进展或不可接受的毒性；治疗时间不超过24个月, 但奥沙利铂最多给药8个周期。 结果. 无进展生存期（PFS）风险比为1.17[95%置信区间（CI）：0.71‐1.93；p=0.548]。实验组和对照组的中位PFS分别为12个月和11.9个月。总生存期风险比为0.97（95% CI：0.46‐2.1；p=0.943）。Parsatuzumab组和安慰剂组的总缓解率分别为59%和64%。两组间的不良事件特征谱相似。 结论. 没有证据支持Parsatuzumab联合贝伐单抗和化疗一线治疗mCRC的疗效。